Demonstrações geométricas no ensino fundamental: uma proposta didática para as séries finais - Rocha, Fabricia Omena (2015)
This paper proposes a teaching sequence using the Mathematical Logic as a teaching method. The teaching of mathematics in primary education has, among other flaws, the lack of methodologies to establish links between the contents studied. Students are "trained" to mechanically answer questions using standard formulas. The study of mathematical logic for Elementary School emphasizes logical thinking of students as well as build this bond as required in the process of teaching and learning, and encourages the full development of mathematical skills and understanding of the world. The student has the opportunity to make connections between the concepts studied and justify the calculations made, strengthening learning and helping to memorize the concepts that context, the didactic proposal brings the logic associated with geometry concepts, the student becomes responsible for their learning. Retracing the steps of Euclid, Pythagoras and Thales, bringing the problems and rebuilding the statements made by them. The choice of geometric concepts was due to destruction often such content related to other issues. The teaching of geometry comes down to context of arithmetic or algebra activities. Rebuild concepts from its history or handling of objects stimulates thinking and promotes cognitive development, as desired by teachers of various forms of education.